2006
DOI: 10.21236/ada451512
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Induced BioEffects

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Heickelen and co-workers have found that chain induced photooxidation occurs for all of the chlorinated ethenes except vinyl chloride [56]. In the liquid phase PCO of chloroform, the rate of oxidation is first order with respect to chloroform concentration, however, in the gas phase at high concentration, the rate is second order with respect to chloroform concentration due to the C1-sensitized reaction [13].…”
Section: Reaction Rate and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Heickelen and co-workers have found that chain induced photooxidation occurs for all of the chlorinated ethenes except vinyl chloride [56]. In the liquid phase PCO of chloroform, the rate of oxidation is first order with respect to chloroform concentration, however, in the gas phase at high concentration, the rate is second order with respect to chloroform concentration due to the C1-sensitized reaction [13].…”
Section: Reaction Rate and Mechanismmentioning
confidence: 99%
“…About 60 installations world wide are using this technology treating diverse effluents from various industries such as petrochemical, pulp and paper, pharmaceutical, cosmetics including waste water and waste treatment facilities [77]. Blystone et al (1993) [56] observed the effective removal and decomposition of several VOCs (TCE, PCE, 1, 1 -dichloroethene, chloroform, and methyl chloride) by a xenon flash lamp. Solarchem high power density lamp was used to treat toluene and TCE in air streams [62].…”
Section: Mb Raymentioning
confidence: 99%